Stock market volatility: friend or foe?. (30th October 2019) - Dempsey, Michael; Gunasekarage, Abeyratna; Truong, Thanh Tan
Abstract: Although a good deal of research effort has been allocated to understanding the time‐series volatility of stock returns – as both market (or systematic) volatility and idiosyncratic (or non‐systematic) volatility – the relationship of such volatility with cross‐sectional volatility or dispersion of outcomes is sparse. Nevertheless, the quest to understand one must involve the quest to understand the other. In this paper, we investigate the dispersion of returns in relation to inter‐temporal volatility, as well as the dynamic of dispersion of returns in generating a portfolio's return outcome. We find that the level of such dispersion is highly significant for portfolio performance and the notion of risk.